PEMBELAJARAN ARANSEMEN LAGU DAERAH SETEMPAT DI SMAN 3 KOTA SOLOK - Yudhi Agus Surahman; Esy Maestro; Erfan Erfan (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe the learning process of the local folk songs arrangement in senior high school number 3 Solok. The study was descriptive by using qualitative approach. As for the implementation of learning process of local folk songs arrangements can be explained as follows: at the first meeting, the teacher explained material about local folk songs arrangements ranging from definition of arrangement, how to arrange, and elements in a song. At the second meeting, the teacher demonstrated the song Mudiak Arau as material on learning process, students were required to be able to sing because before arranging the students must know the songs that will be arranged. At the next meeting, the teacher grouped the students to give task. Then, at the last meeting, the students were asked to write and sing the results from each group. The results of this research were, the learning of art and culture subject especially material in the music arts at senior high school number 3  Solok ran well. The learning of local folk song arrangement at that school was implemented by using lecturing and group discussion method. On each group of students, they have a form of arrangement with a different intro to each group by writing the notation numbers. It can be concluded that the learners have understood enough toward the arrangement of local folk song material enough  and it was revealed by the tasks given by the teacher, also students were able to do the tasks well. Keywords: Arts and culture, Music Arts, Arrangement